Evaluation of Compliance in Control and Prevention Study of Vancomycin Resistant Enterococcus Outbreak - Vuslat Kecik Bosnak; Mustafa Namiduru; Ilkay Karaoglan; Ayse Ozlem Mete (The Scientific World Journal)
Objective. Vancomycin resistant enterococci (VRE) colonization and the spread decrease with compliance and isolation guidelines. For the isolation methods to succeed, compliance with the isolation guidelines needs to be overseen. In this study, VRE outbreak among the Pediatric Ward patients, the preventative efforts to control this outbreak, and the impact of scoring tables used in controlling this outbreak on the success are explained. Design. Rectal swab cultures were taken from patients who were admitted to the Ward between October and December 2010 due to diagnoses of VRE and urinary tract infection. Results. VRE were isolated in the rectal swab samples of 34 patients. VRE infection findings were clinically detected in two of the cases with VRE isolation. Two isolations of VRE were detected on cultures from patient room door handle surface and the telephone in the room for common use. Close contact isolation was achieved and barrier precautions were taken for all cases, as soon as the detections were made. A scoring system was developed to evaluate the feasibility of and the compliance with the precautions to be taken. Conclusions. With the method presented in this study, the outbreak at our hospital was under control within two months.